2018
DOI: 10.1007/s00264-018-3878-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, management, and outcomes of spontaneous osteonecrosis of the knee in Indian population

Abstract: Combined therapy of NSAIDs and bisphosphonates shows excellent results over a period of one year. Joint-preserving surgeries are effective even in Koshino stage 3 SPONK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
12
0
2
Order By: Relevance
“…The MRI-based criteria used for the differential diagnosis of SONK were found to be heterogeneous. While some authors screened images for speci c features, such as focal hypointense areas on T1-or T2-weighted images, visible fracture lines or focal epiphyseal contour depressions [7,[13][14][15][16][17][18][19][20][21][22][23][24], others diagnosed SONK in the presence of bone marrow edema (BME) accompanying typical symptoms [25][26][27]. Two case reports radiologically demonstrated the primary overlay of fracture lines by BME [28,29].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The MRI-based criteria used for the differential diagnosis of SONK were found to be heterogeneous. While some authors screened images for speci c features, such as focal hypointense areas on T1-or T2-weighted images, visible fracture lines or focal epiphyseal contour depressions [7,[13][14][15][16][17][18][19][20][21][22][23][24], others diagnosed SONK in the presence of bone marrow edema (BME) accompanying typical symptoms [25][26][27]. Two case reports radiologically demonstrated the primary overlay of fracture lines by BME [28,29].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Sixteen of the twenty-two included studies (73%) reported positive clinical and/or radiological outcomes [7,13,17,[20][21][22][23][25][26][27][28][29][30][31][32][33]. Although RWB was the most thoroughly tested treatment modality, it has also been challenged by some authors.…”
Section: Therapy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Erstbeschreibung der Osteonekrosen am Knie geht auf Ahlbäck (1968) zurück, der eine spontane Osteonekrose (SONK) im lateralen Anteil des medialen Femurkondylus ohne charakteristische Ursachen für eine Osteonekrose beschrieb [21]. Die als klassische SONK oder M. Ahlbäck bezeichnete Erkrankung muss jedoch bei der Diagnosestellung von der sekundären Osteonekrose mit möglicherweise multilokulärer Erscheinung sowie einer post-arthrokoskopischen Osteonekrose des Knies abgegrenzt werden [22]. Mit einer Prävalenz von bis zu 10 % tritt die SONK mit Bevorzugung des weiblichen Geschlechtes bei Patienten über 65 Jahre mit akuten Knieschmerzen auf [23].…”
Section: Fokale Subchondrale Osteonekrosen Am Knieunclassified
“…Während SONK in 94 % im medialen Femurkondylus lokalisiert ist [27], können die sekundäre und post-arthroskopische Osteonekrose auch im lateralen Kniekompartiment bzw. im medialen Tibiaplateau auftreten [22]. Bisweilen ist die Abgrenzung jedoch erschwert, da auch bei der SONK in kleineren Fallserien in bis zu 80 % mediale Meniskusrisse dargestellt werden und eine spontane Genese daher unwahrscheinlich ist [28,29] Pathophysiologisch unterscheidet man zwischen einer toxischvaskulären (sekundäre Osteonekrose) und traumatischen (SONK und postarthroskopisch) Genese.…”
Section: Fokale Subchondrale Osteonekrosen Am Knieunclassified